Biomechanical investigation of osseointegration of loosely and overtightly placed titanium implants - Istek, Ozmen; Tanrisever, Murat; Ozcan, Erhan Cahit; Can, Limit Koray; Altunyuva, Ali Yusuf; Demir, Serbest; Dundar, Serkan (Univ Zulia, Facultad Ciencias Veterinarias, 2025)
The objective of this research was to biomechanically assess the osseointegration of implants placed in bone sites prepared with diameters smaller than, larger than, or equal to the implant weighing between 250-300 g were used in the study. The rats were divided into three groups and titanium implants, 2.5 mm diameter and 4 mm lenght, were placed in the cortico-cancellous bone structure in the metaphyseal parts of the right tibia bones of all rats included in the study. The study groups were; the group in which a bone bed of 2.2 mm in diameter and 4 mm in length was prepared and the implants were placed very tightly (n=7), the group in which a bone bed of 2.8 mm in diameter and 4 mm in
Keywords: Bone implantation; biomechanical measurement